Does illegal immigration harm society? - Barbour, Scott (In controversy, 2010)
Historical overview of the illegal immigration controversy -- Does illegal immigration harm the American economy? -- Does illegal immigration harm American culture? -- Does illegal immigration lead to increased crime and terrorism? -- How should the government address the issue of illegal immigration?